2019
DOI: 10.35940/ijrte.d9992.118419
|View full text |Cite
|
Sign up to set email alerts
|

Hereford and Simmental Cattle Breeds in Siberia: Implementation of the Adaptive and Productive Potential in the Cold Climate

Abstract:  Abstract:This study was aimed at studying the biological characteristics of the calves of the Hereford and Simmental breeds, and crosses of these breeds in Siberia. The article discusses the peculiarities of metabolism and utilization of nutrients, growth rate, meat productivity and quality, feed conversion in groups of calves up to 15.5 months of age due to the breed identity in the keeping conditions in light facilities and cold climate. Similarity has been noted in the parameters of gas-and-energy metabol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 10 publications
0
6
0
2
Order By: Relevance
“…The identification of genes controlling production traits in farm animal species will lead to cost-effective genetic testing of entire populations for the enhanced selection of individuals, thus providing increased product quality and production efficiency. Sellick et al (2007) stated that "A previously reported transversion in MSTN (AF320998.1, g.433C>A), resulting in the amino acid substitution of phenylalanine by leucine at position 94 of the protein sequence (F94L), was the only polymorphism consistently related to increased muscling. Overall the size of the g.433C>A additive effect on carcass traits was moderately large, with the g.433A allele found to be associated with a 5.5 % increase in silverside percentage and eye muscle area (EMA) and a 2.3 % increase in total meat percentage relative to the g.433C allele.…”
Section: The F94l Mstn Genotyping Displayed the Existence Of Meat Promentioning
confidence: 99%
See 4 more Smart Citations
“…The identification of genes controlling production traits in farm animal species will lead to cost-effective genetic testing of entire populations for the enhanced selection of individuals, thus providing increased product quality and production efficiency. Sellick et al (2007) stated that "A previously reported transversion in MSTN (AF320998.1, g.433C>A), resulting in the amino acid substitution of phenylalanine by leucine at position 94 of the protein sequence (F94L), was the only polymorphism consistently related to increased muscling. Overall the size of the g.433C>A additive effect on carcass traits was moderately large, with the g.433A allele found to be associated with a 5.5 % increase in silverside percentage and eye muscle area (EMA) and a 2.3 % increase in total meat percentage relative to the g.433C allele.…”
Section: The F94l Mstn Genotyping Displayed the Existence Of Meat Promentioning
confidence: 99%
“…The phenotypic effects of the g.433A allele were partially recessive". Probably the MSTN genotype can produce an intermediate, non-double-muscling phenotype, which should be of significant value for beef cattle producers (Sellick et al, 2007).…”
Section: The F94l Mstn Genotyping Displayed the Existence Of Meat Promentioning
confidence: 99%
See 3 more Smart Citations